2016
DOI: 10.1111/1541-4337.12206
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Overview of the Risks and Benefits of Coffee Consumption

Abstract: Findings on both the health benefits and the potentially harmful effects of coffee consumption have been contradictory. However, the general scientific consensus is that moderate, regular coffee drinking by healthy individuals is either essentially benign or mildly beneficial. Results and generalizations are complicated by a number of factors, including differences in age, gender, health status, type of coffee preparation, serving size, and source of coffee. Coffee may have potential health benefits and risks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 206 publications
1
23
0
Order By: Relevance
“…Reduced risk of liver injury Individuals consuming more than two cups of coffee or tea daily are less likely to suffer from chronic liver diseases as compared to the ones consuming one cup of coffee daily Wolde (2014) Coffee (source of caffeine) has protective role against non-alcoholic cirrhosis, as it antagonizes the effect of hepatitis B and C infection Cadden et al (2007), George et al (2008), Pourshahidi et al (2016) 7…”
Section: Caffeine Labellingmentioning
confidence: 99%
“…Reduced risk of liver injury Individuals consuming more than two cups of coffee or tea daily are less likely to suffer from chronic liver diseases as compared to the ones consuming one cup of coffee daily Wolde (2014) Coffee (source of caffeine) has protective role against non-alcoholic cirrhosis, as it antagonizes the effect of hepatitis B and C infection Cadden et al (2007), George et al (2008), Pourshahidi et al (2016) 7…”
Section: Caffeine Labellingmentioning
confidence: 99%
“…However, recent studies relating coffee/caffeine consumption to health problems. However, in up to date years, most research has suggested that coffee actually has health benefits [4][5][6]. The caffeine in coffee is a bioactive compound with stimulatory property on the central nervous system and a positive outcome on long-term memory.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Coffee consumed by millions of people every day and various scientific studies have been conducted to check the relationship between coffee consumption and a wide range of chronic diseases and health risk, in addition to total death, lots of cancers, cardiometabolic risk, liver disorders, and neurological situation. These properties have been certified due to many different bioactive constituents of coffee, as well as caffeine (methylxanthine), chlorogenic acids (polyphenol), diterpenes, and other phenolics, among these, may also potentially have additive or synergistic effects [6].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted to examine the relationship between coffee consumption and a wide range of chronic diseases ( 1 ) . Links between coffee consumption and cardiometabolic health have been widely reported in the literature but with equivocal results ( 2 4 ) .…”
mentioning
confidence: 99%